2021
DOI: 10.1002/mde.3527
|View full text |Cite
|
Sign up to set email alerts
|

Omnichannel service operations with order‐online‐and‐dine‐in‐store strategy

Abstract: This study develops a game theory model to study the effects of the order‐online‐and‐dine‐in‐store (OODS) strategy on a restaurant's optimal decisions, expected profits, and the environment. We analyse and compare the equilibrium solutions under the benchmark and the online‐to‐offline scenario using the OODS strategy. The results show that the restaurant benefits from the OODS strategy when the operating costs of online channel and physical store are relatively low or when the unit carbon tax price of food pac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
(63 reference statements)
0
0
0
Order By: Relevance
“…Zhang et al [39] studied the impact of price subsidies on product pricing and revenue in a single channel supply chain, as well as the impact of price subsidies and fairness concerns on supply chain revenue in a dual giant supply chain. Guo et al [40] studied the impact of online ordering and in-store dining strategies on restaurant optimal decision-making and maximum profit; they found that when the unit carbon tax price is relatively high, using this strategy can reduce carbon tax costs. Du et al [41] discussed four combinations of the pricing strategies (online and offline unified pricing and differential pricing) and delivery modes (self-distribution and platform distribution) of restaurants.…”
Section: O2o Supply Chain Pricing Strategiesmentioning
confidence: 99%
“…Zhang et al [39] studied the impact of price subsidies on product pricing and revenue in a single channel supply chain, as well as the impact of price subsidies and fairness concerns on supply chain revenue in a dual giant supply chain. Guo et al [40] studied the impact of online ordering and in-store dining strategies on restaurant optimal decision-making and maximum profit; they found that when the unit carbon tax price is relatively high, using this strategy can reduce carbon tax costs. Du et al [41] discussed four combinations of the pricing strategies (online and offline unified pricing and differential pricing) and delivery modes (self-distribution and platform distribution) of restaurants.…”
Section: O2o Supply Chain Pricing Strategiesmentioning
confidence: 99%